Formalisasi Islam dalam Kebijakan Pendidikan Daerah di Indonesia: Antara Spirit Religius dan Rasionalitas Birokrasi - Hajar, Salwa; Musyarofah, Umirul; Muhammad Ikbal Fahlehfi; Kamil Sahri, Iksan (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
The increasing integration of Islamic values into regional education policies in Indonesia reflects a new dynamic between public spirituality and the rationality of government bureaucracy. While previous studies have examined sharia-based regulations from political and legal perspectives, few have specifically explored how Islamic values are formalized within regional education policies. This article aims to analyze the forms and patterns of Islamic formalization in education policies across four regencies in East Java (Jombang, Ponorogo, Pasuruan, and Lamongan) by emphasizing the balance between religious spirit and administrative rationality. Using a qualitative-normative approach and the systematic literature review method, this study examines regional policy documents, national legislation, and relevant empirical research. The findings indicate that local governments institutionalize Islamic values through educational regulations oriented toward strengthening religious character, such as compulsory diniyah education, Qur’anic literacy programs, and habitual religious activities in schools. This process represents the rationalization of spirituality, wherein religious values are translated into measurable administrative frameworks without losing their moral essence. Conceptually, the formalization of Islam in education policy illustrates a synthesis between public morality and modern governance; practically, it contributes to the enhancement of students’ moral character and the harmonization between religious society and educational bureaucracy. The study recommends a mixed-methods approach for future research to assess the empirical impact of Islamic-based education policies on the quality and character development of students at the regional level.